The Effect of Workload and Cyberloafing on Employee Performance at the Communication and Informatics Service of Central Mamuju Regency - Windarti Tasni; Muh Ferils; J. Fuji Inzani SL (Jurnal Economic Resource, 2025)
The aim of this research is to determined the effect of workload and cyberloafing on employee performance at the Central Mamuju Regency Communication and Information Service. The method used in this research is quantitative research, with a total sampling technique. The research population was all employees of the Central Mamuju Regency Communication and Information Service with a sample size of 38 people. Data collection methods were carried out through surveys, interviews, documentation, and distributing questionnaires to respondents. Data processing techniques include validity testing and instrument reliability testing. Data analysis was carried out using multiple linear regression, while hypothesis testing used partial tests (t tests) and simultaneous tests (f tests). The contribution of the independent variable to the dependent variable is analyzed using the coefficient of determination (R²). The research results show that workload (X1) has a partial and significant positive effect on the performance (Y) of employees of the Central Mamuju Regency Communication and Informatics Service, Cyberloafing (X2) has a partial and significant negative effect on the performance (Y) of employees of the Central Mamuju Regency Communication and Informatics Service and workload (X1) and cyberloafing (X2) have a simultaneous and significant effect on the performance (Y) of employees of the Central Mamuju Regency Communication and Informatics Service.